Elevated, combined serum free light chain levels and increased mortality: a 5-year follow-up, UK study. Issue 11 (25th August 2012) - Anandram, Seetharam; Assi, Lakhvir Kaur; Lovatt, Tracy; Parkes, Jayne; Taylor, Joanne; Macwhannell, Alan; Jacob, Abraham; Handa, Sunil; Harding, Stephen; Basu, Supratik
Abstract : Aims: Abnormal serum free light chain (FLC) ratios are diagnostically important in almost all plasma cell disorders. However, absolute increases in polyclonal FLC levels are often discarded as inconsequential. Here we report an association between increased combined polyclonal FLC (cFLC: FLCκ plus FLCλ) concentrations and mortality. Methods: 723 patients sent for 30 routine haematological assessments were enrolled. Patients with a confirmed monoclonal gammopathy were removed. The remaining 527 patients were followed up for up to 4.5 years. Statistical analysis was performed using SPSS (V.19). Results: During follow-up, there were 99 deaths (18.8%). Kaplan-Meier survival analysis revealed 29% of these deaths occurred within the first 100 days (N=29). Multivariate analysis identified only cFLC >65 mg/l, albumin <33 g/l and  estimated glomerular filtration rate <30 ml/min/1.73 m 2 to be independently associated with mortality within 100 days and 4.5 years with, cFLC having the highest HR of 7.1. A simple risk stratification model based only on albumin and cFLC identified 86% mortality within 100 days and 62% over 4.5 years. Conclusions: Elevated cFLC is significantly associated with increased mortality and with albumin can be used to identify patients at risk of mortality at 4.5 years with high-risk patients detected within 100 days.